The Influence Of Tax Socialization, Tax Understanding, And Tax Rates On The Compliance Of UMKM Taxpayers At The Palembang Ilir Timur Pratama Tax Service Office - Faradilla, Damayanti; Wijaya, Angka; Ikraam, Ikraam (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Micro, small, and medium companies (MSMEs) registered at the KPP Pratama Palembang llir Timur were the subjects of this research, which aimed to identify the relationship between taxpayer compliance and factors such as tax socialization, tax comprehension, and tax rates. The author of this research used a technique that focused on numerical data by surveying a representative sample of the community. The final tally, reached with a 95% confidence level using the Isaac and Michael method, includes 342 respondents in total. The data were analyzed using multiple linear regression with the help of SPSS version 23 to evaluate the influence of each independent variable on the dependent variable. The findings indicate that taxpayers’ comprehension of tax regulations and the applied tax rates have a significant impact on MSME compliance, while efforts in tax socialization appear to have no notable effect.